Politieke en sosiale vraagstukke in die prediking - Dreyer, T. F. J. (Hervormde teologiese studies, 1986)
Political and social issues in preaching This paper is an attempt to provide guidelines for preaching with regard to the socio-political aspects of society. The dangers of political preaching as an enigma of contemporary preaching are analysed. Preaching is a complicated process relating to hermeneutics and communication. Obstacles in disturbing this process are pinpointed in the study. The paper's aim is to find ways to overcome the disturbance of the normal hermeneutical process, especially where political aspects are concerned.